Efektifitas Model Discovery Learning Berbasis Media Audio Visual Terhadap Hasil Belajar IPA Siswakelas V SDN 081 Palembang - Vinanda, Efrisa Jelsi; Aryaningrum, Kiki; Fakhrudin, Ali (ANTHOR: Education and Learning Journal, 2022)
This study aims to determine the effectiveness of the application of discovery learning models based on audio-visual media on the science learning outcomes of fifth grade students at SDN 081 Palembang. The sample in this study were students of class VA as the experimental class and students of class VB as the control class. The number of samples in this study were 30 students in each class. The type of research used in this research is experimental research with a quasi-experimental research method with a nonequivalent control group design. Data collection techniques were carried out using tests, observationsand documentation. The instrument used in the science learning outcome test is in the form of a multiple choice test. The data analysis technique was carried out using the t-test and the N-Gain test. The results of the hypothesis test obtained that the value of tcount 5.90 and ttable 2.00172 so that Ho was rejected and Ha was accepted, and seen from the results of the N-Gain test in the experimental class including the moderate category, namely 0.61 while inthe control class the results of the N-Gain test with the low category is 0.23, it can be concluded that the effectiveness of the application of the discovery learning model based onaudio-visual media has a significant effect on the science learning outcomes of fifth grade students at SDN 081 Palembang.